2017
DOI: 10.24271/garmian.217
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of Polyvinyl Alcohol Films doped with Fe

Abstract: FeCl 3 was used as a source of Fe that added to the PVA films. PVA-Fe films were prepared by casting method. The UV-Visible spectrophotometer used to record the absorbance spectrum in the range of 300-900 nm. The absorbance decreased with the increasing of Fe in the PVA films. The absorption coefficient increased with the increasing of Fe content, while the extinction coefficient, refractive index and optical conductivity are decreased. The optical conductivity decreased from 4 eV for PVA film to 3.3 eV for PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Many scientists have reported that polymer nanocomposites ofPVA and PEGhave attracted more attention due to their optical properties and theability to produce hydroxyl group which leads to optical nonlinearity [6][7][8][9][10]. In this article the synthesis, characteristics and third order NLO properties of silicon/PVA-PEG nanocomposites are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Many scientists have reported that polymer nanocomposites ofPVA and PEGhave attracted more attention due to their optical properties and theability to produce hydroxyl group which leads to optical nonlinearity [6][7][8][9][10]. In this article the synthesis, characteristics and third order NLO properties of silicon/PVA-PEG nanocomposites are presented.…”
Section: Introductionmentioning
confidence: 99%